Comparative Masticatory Performance of Bilateral Balanced Occlusion and Lingualized Occlusion in Complete Denture Patients - Umair Wali Khan, Akhtar Zeb, Muhammad Babar Sultan, Babar Ali Khan, Zohaib Ur Rehman Mufti, Ghazala Shaheen, Sara Mannan, Tahira Shamim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Both natural and artificial dentition has an occlusal scheme defined by the shape and positioning of the occlusal contacts. Complete denture fabrication has used a variety of occlusal designs that might have impact on stability of denture and masticatory function. Objective: To determine comparative masticatory performance of bilateral balanced occlusion and lingualized occlusion in complete denture patients Methodology: This study design was randomized trial carried out at the department of Prosthodontics, Altamash Institute of Dental Medicine for duration of six months. A total of 80 subjects were enrolled in the current study and were divided into two groups. Forty subjects were included in each group. In group LO subjects, complete dentures were provided with Lingualized occlusion whereas in group BBO participants, complete dentures were provided with bilateral balanced occlusion. All the required information’s including demographic features were documented in a predesigned Performa. SPSS version 19 was used to enter and analyze all of the data. Results: The mean weight of masticated peanuts in group LO was 5.30gm with standard deviation of 0.89 while in group BBO, the mean weight of masticated peanuts was 9.45gm with standard deviation of 2.10. The difference was significant statistically between two occlusions schemes (p=0.021). Conclusion: Our study concludes that masticatory efficiency was higher in complete dentures patients with lingualized occlusal than bilateral balanced occlusal scheme..